Increased Prolonged Sitting in Patients with Rheumatoid Arthritis during the COVID-19 Pandemic: A Within-Subjects, Accelerometer-Based Study - Pinto, Ana Jessica; Rezende, Diego; Sieczkowska, Sofia Mendes; Meireles, Kamila; Bonfiglioli, Karina; Ribeiro, Ana Cristina de Medeiros; Bonfá, Eloisa; Owen, Neville; Dunstan, David W.; Roschel, Hamilton; Gualano, Bruno (International journal of environmental research and public health, 2023)
Background: Social distancing measures designed to contain the COVID-19 pandemic can restrict physical activity, a particular concern for high-risk patient groups. We assessed rheumatoid arthritis patients’ physical activity and sedentary behavior level, pain, fatigue, and health-related quality of life prior to and during the social distancing measures implemented in Sao Paulo, Brazil. Methods: Post-menopausal females diagnosed with rheumatoid arthritis were assessed before (from March 2018 to March 2020) and during (from 24 May to 7 July 2020) social distancing measures to contain COVID-19 pandemic, using a within-subjects, repeated-measure design. Physical activity and sedentary behavior were assessed using accelerometry (ActivPAL micro). Pain, fatigue, and health-related quality of life were assessed by questionnaires. Results: Mean age was 60.9 years and BMI was 29.5 Kg/m2. Disease activity ranged from remission to moderate activity. During social distancing, there were reductions in light-intensity activity (13.0% [−0.2 h/day, 95% CI: −0.4 to −0.04; p = 0.016]) and moderate-to-vigorous physical activity (38.8% [−4.5 min/day, 95% CI: −8.1 to −0.9; p = 0.015]), but not in standing time and sedentary time. However, time spent in prolonged bouts of sitting ≥30 min increased by 34% (1.0 h/day, 95% CI: 0.3 to 1.7; p = 0.006) and ≥60 min increased by 85% (1.0 h/day, 95% CI: 0.5 to 1.6). There were no changes in pain, fatigue, and health-related quality of life (all p > 0.050). Conclusions: Imposed social distancing measures to contain the COVID-19 outbreak were associated with decreased physical activity and increased prolonged sedentary behavior, but did not change clinical symptoms sitting among patients with rheumatoid arthritis.